Outlaw’s redemption - Bourne, Lena (knjige, 2021)
SaraIan and Sara. Sara and Ian. That’s how it’s always been, since the sixth grade, and definitely since before I knew what love really is. And I do love him, I’ll never stop. I realize it again each time I try to run from him. But I ran regardless once I found out I was pregnant. I just didn’t go far enough. I can’t, because he’s always with me, in my heart, and you can’t escape what’s in your heart. Only now I have my child to consider, and the last thing anyone needs is a father like Ian. He can never know about our child. Sometimes a bad boy is just that…bad. And there’s no hope of ever changing them. I know, because I tried.Now Ian is out of prison, and he wants me back. This time he won’t succeed, and all my fantasies of running my hands down his perfect body, or staring into his baby blue eyes won’t change that. Because in real life, beasts don’t turn into princes when you kiss them. Now if I could just stop wanting to keep kissing him.